PENGEMBANGAN MEDIA AUDIO LAGU ANAK USIA 4-6 TAHUN DI LEMBAGA PAUD AN-NURR - Wulandari, Rina (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Teachers as one of the stimulators of music in children is supposed to provide stimulation in accordance with the stages of child development. Related to this, the observations obtained in the field of human resources issues that early childhood teachers in the field of art music in general, causing minimal experience obstacles when introducing the song in children. This study tries to answer questions related to the field of media development need for the audio track of children. The research approach using a model of development recording music using cool edit pro from Purwacandra (2007). The result are audio media children song in the An-Nurr that according to child development capabilities related to music.